2011
DOI: 10.3109/10428194.2011.572323
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced invasiveness in multidrug resistant leukemic cells is associated with overexpression of P-glycoprotein and cellular inhibitor of apoptosis protein

Abstract: Multidrug resistance (MDR) and multi-organ infiltration are the major obstacles to the successful treatment of leukemia. It is known that the drug efflux protein, P-glycoprotein (P-gp), and inhibitors of apoptosis proteins (IAPs) are involved in the MDR of leukemic cells, but their roles in leukemia infiltration have not been clearly elucidated. In this study, leukemic cell lines K562 and HL60 and their MDR variants K562R and HL60R have been used to analyze their infiltrative ability. MDR variants display enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 32 publications
0
24
0
Order By: Relevance
“…7). PKCs have been implicated in the biology of AML (55) and can contribute to the resistance to chemotherapeutic drugs by interfering with the cell response triggered by these drugs or by increasing their clearance as a result of activating P-glycoprotein (56,57). Here we provide evidence that PKCs may also be implicated in AML resistance to different kinase inhibitors for the first time.…”
Section: Phosphoproteomics Of Basal and Drug-treated Aml Cellsmentioning
confidence: 69%
“…7). PKCs have been implicated in the biology of AML (55) and can contribute to the resistance to chemotherapeutic drugs by interfering with the cell response triggered by these drugs or by increasing their clearance as a result of activating P-glycoprotein (56,57). Here we provide evidence that PKCs may also be implicated in AML resistance to different kinase inhibitors for the first time.…”
Section: Phosphoproteomics Of Basal and Drug-treated Aml Cellsmentioning
confidence: 69%
“…Studies of pediatric ALL and AML cells did not demonstrate a definitive link between P-gp and BCRP expression and drug resistance in vitro (Svirnovski et al, 2009). However, studies with leukemia cell lines and severe combined immunodeficiency mouse xenograft models demonstrated that P-gp overexpression may be associated with enhanced leukemia cell invasiveness (Hu et al, 2011).…”
Section: Mdr Proteins Conferring Resistance In Preclinical In Vitro Mmentioning
confidence: 99%
“…PKC isozymes and cancer, PKC isozymes, especially PKC and , are involved in the Pgp-mediated MDR in several types of cancer, such as colon cancer [119][120][121], pancreatic cancer [399], gastric cancer [157], breast cancer [55], leukemia [513], and prostate cancer [447]. In general, inhibition of PKC isozymes that regulate P-gp leads to reduced MDR and enhanced cancer cell apoptosis.…”
Section: Pkc Isozymes and Mdrmentioning
confidence: 99%